2018
DOI: 10.1021/acsami.8b11684
|View full text |Cite
|
Sign up to set email alerts
|

Heterobinuclear Light Absorber Coupled to Molecular Wire for Charge Transport across Ultrathin Silica Membrane for Artificial Photosynthesis

Abstract: Coupling of robust, all-inorganic heterobinuclear light absorbers to metal oxide catalysts for water oxidation across an ultrathin product-separating silica membrane requires charge transfer through organic molecular wires embedded in the silica. A synthetic approach for assembling the bimetallic units on the silica surface is introduced that is compatible with the presence of encapsulated organic molecules. Accurate selection and fine tuning of the concentration of embedded conducting wires are enabled by a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(34 citation statements)
references
References 43 publications
2
32
0
Order By: Relevance
“…To this end, we have recently introduced ultrathin silica layers with embedded molecular wires as gas impermeable, charge and proton conducting membranes . Controlled charge transport across ultrathin insulating silica membranes was achieved by embedded molecular wires ( p ‐oligo(phenylene vinylene)), which were characterized by short circuit photoelectrochemical and ultrafast optical measurements . Such a functional silica nanomembrane separating incompatible inorganic and microbial environments was demonstrated …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To this end, we have recently introduced ultrathin silica layers with embedded molecular wires as gas impermeable, charge and proton conducting membranes . Controlled charge transport across ultrathin insulating silica membranes was achieved by embedded molecular wires ( p ‐oligo(phenylene vinylene)), which were characterized by short circuit photoelectrochemical and ultrafast optical measurements . Such a functional silica nanomembrane separating incompatible inorganic and microbial environments was demonstrated …”
Section: Introductionmentioning
confidence: 99%
“…[16,17] Controlled charge transport across ultrathin insulating silica membranes was achieved by embedded molecular wires (p-oligo(phenylene vinylene)), which were characterized by short circuit photoelectrochemical and ultrafast optical measurements. [18][19][20][21][22][23] Such a functional silica nanomembrane separating incompatible inorganic and microbial environments was demonstrated. [18] Proton transport and gas permeability properties based on cyclic voltammetry (CV) measurements have recently been reported for single oxide nanolayers such as ultrathin silica prepared by atomic layer deposition (ALD) [18,24] or ozone treatment of spin-cast Si precursor, [7] or for chromia nanolayers prepared by solution-based photo-or electrodeposition methods.…”
mentioning
confidence: 99%
“…7 Proton conductivity across the 2 nm silica membrane was quantified by electrochemical impedance spectroscopy and found to exceed the flux needed under maximum solar intensity by three orders of magnitude, and cyclic voltammetry confirmed that the silica nanolayer completely blocks O 2 from crossing the membrane. 8 While visible light driven electrochemical and transient optical monitoring of charge transport demonstrates that a substantial fraction of embedded wire molecules span the silica nanolayer so as to function as charge conduits, [3][4][5][6] experimental information on the orientation of anchored wires is lacking. Here, we report an infrared spectroscopic study of wire molecules anchored on planar Co 3 O 4 and embedded in ultrathin silica layers by polarized Fourier transform-infrared reflection-absorption spectroscopy (FT-IRRAS) and non-polarized grazing angle attenuated total reflection Fourier transform-infrared spectroscopy (GATR FT-IR).…”
Section: Introductionmentioning
confidence: 99%
“…21 Structural identification of the ALD layer as amorphous SiO 2 is confirmed by the characteristic longitudinal optic (LO) SiOSi asymmetric stretch at 1226 cm -1 in the FT-IRRAS shown in Figure 2(a) trace (1). 14 Cross sectional HR-TEM and AFM images of silica nanolayers deposited by the plasma-enhanced ALD method on Pt reported in a previous paper demonstrate uniformity, 22 attachment to the silica layer, TMSA was anchored on the SiO 2 surface followed by reaction with a carboxylic group of the dcbpy ligand to form an amide bond using the same method described above for PV3 attachment to anchored silyl aniline.…”
Section: Anchoring Of 4-(trimethoxysilyl)aniline (Tmsa) or 4-(trimethoxysilyl)benzyl Azidementioning
confidence: 88%
“…8,9 The amorphous silica shell of 2-3 nm thickness that surrounds the Co oxide nanotube blocks O 2 and other small molecules from crossover, while molecular wires (oligo(p-phenylenevinylene)) made of 3 aryl units, abbreviated as PV3) embedded in the silica control charge transfer from light absorbers on the outside of the silica shell to the Co 3 O 4 catalyst on the inside. [10][11][12][13][14][15][16][17] Furthermore, stacked Co 3 O 4 and SiO 2 nanolayers were shown to transmit protons at rates that exceed by far those needed to keep up with the solar flux at maximum intensity. Hence, the flow of protons generated by H 2 O oxidation on the Co 3 O 4 surface through the oxide nanowall to the sites of CO 2 reduction on the opposite side does not pose efficiency limitations under artificial photosynthesis conditions.…”
Section: Introductionmentioning
confidence: 99%